Comparison of intraocular lens decentration parameters after femtosecond and manual capsulotomies - Nagy, Zoltán Zsolt; Kránitz, Kinga; Takacs, Agnes I.; Miháltz, Kata; Kovács, Illés; Knorz, Michael C. (Journal of refractive surgery, 2011)
PURPOSE: - - To evaluate a laser technique and manual technique to perform capsulorrhexis in cataract eyes. - - METHODS: - - Anterior capsulotomy was performed with an intraocular femtosecond laser (LenSx Lasers Inc) in 54 eyes (FS group) and manual continuous curvilinear capsulorrhexis was performed in 57 eyes (CCC group). Circularity and area of capsulotomy and IOL decentration were measured using Photoshop CS4 Extended (Adobe Systems Inc) 1 week after surgery. Average keratometry, axial length, and preoperative anterior chamber depth were examined with the Lenstar LS 900 (Haag-Streit AG). - - RESULTS: - - No statistically significant differences were noted between groups in axial length, preoperative refractive state, and in the area of capsulotomy. Circularity values were significantly better in the FS group (P=.032). We found incomplete overlap of capsulotomies in 28% of eyes in the CCC group and 11% in the FS group (P=.033). Significant correlations were noted between axial length and area of capsulotomy, and between average keratometry and area of the capsulotomy in the CCC group (R=0.278, P=.036; and R=−0.29, P=.033, respectively), but both did not correlate in the FS group (P>.05). In the CCC group, the pupillary area correlated significantly with the area of the capsulotomy (R=0.27, P=.039). Significant correlation was noted between IOL decentration and axial length in the CCC group (R=0.30, P=.026), but there was no correlation in the FS group (P>.05). - - CONCLUSIONS: - - Femtosecond laser capsulorrhexis was more regularly shaped, showed better centration, and showed a better intraocular lens/capsule overlap than manual capsulorrhexis.
Gesehen am 15.09.2022